Physical long-term conditions and the effectiveness of England’s NHS Talking Therapies programme for working-age adults: findings from a South London borough - Matthew Broadbent; Matthew Hotopf; Brendon Stubbs; Lisa Harber-Aschan; Stephani Hatch; David Armstrong; Ioannis Bakolis; Alex Dregan; Amy Ronaldson; Nicusor Sima (BMJ Mental Health)
Objective To assess the effectiveness of NHS Talking Therapies (NHSTT) service for working-age adults with mild to moderate depression or anxiety and to evaluate the impact of multiple physical long-term conditions (LTCs) on treatment outcomes.Method We have linked routinely collected data from the NHSTT services in South London (UK) with primary care data for aged 18–64 years who had accessed the services between August 2008 and March 2021. The main outcome measures were NHSTT service key performance indicators of ‘recovery’ and ‘reliable improvement’. Multiple and specific physical LTCs represented the exposure of interest. Cox proportional hazard models were used to assess associations between physical LTC exposures and outcomes.Findings Among 35 814 adults (mean age=37, 67% women) attending the NHSTT, physical LTCs were associated with moderately lower ‘recovery’ rate (adjusted HR (aHR)=0.91, 95% CI 0.88 to 0.95) relative to no LTCs. A dose–response relationship was also observed: the likelihood of ‘recovery’ decreased with the number of physical LTCs (one condition: aHR=0.95, 95% CI 0.91 to 0.98; two conditions: aHR=0.88, 95% CI 0.83 to 0.93; three conditions: aHR=0.82, 95% CI 0.75 to 0.91; four or more conditions: aHR=0.72, 95% CI 0.61 to 0.85).Conclusion Among working-age adults, the effectiveness of NHSTT services varied with the number and type of physical LTCs. These findings highlight the need for tailored interventions for patients with multiple physical LTCs to improve treatment outcomes.